Pricing of Sorghum Irrigation Water: A Comparison between Gravity, Spate and Rain-fed Irrigations in Sudan - B, Eltigani E; Gali, Mohamed E (Gezira Journal of Economic and Social Sciences; مجلد 6 عدد 2 (2015), 2015)
There is global consensus to use scientific approaches to value all natural resources including water resources. Valuation of water is one way of making users more aware of its value. The aims of this paper is to determine the value of water used in agriculture under gravity system in Gezira Scheme and spate irrigation systems in Gash Delta Agricultural Corporation in Sudan. CROPWAT model was used to determine the volume of water supplied for irrigation. Net revenue was calculated to determine the output from agriculture. The main results show that the net values of water are $0.005/m 3 and $ 0.001/m 3 under gravity and spate irrigation systems respectively. The value of water used in gravity irrigation system is greater than water used in spate irrigation system. These findings will help into setting real value and cost of water in agriculture as the major consumptive sector and hence will help policy makers in developing decisions on agricultural water.